The effect of addition of chitosan nano gel on denture base materials heat polymerized acrylic resin on impact strength: Study experimental - Adillah, Afif; Zulkarnain, Muhammad; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Heat-polymerized acrylic resin (HPAR) is the most widely used denture base material for denture bases due to several advantages, including non-toxicity, biocompatibility, availability, and has good aesthetics. However, HPAR has a significant drawback, specifically low impact strength, especially with long-term denture use, which necessitates the addition of a reinforcing material such as chitosan nano gel. The aim of this study was to analyze the effect of adding chitosan nano gel on the impact strength of HPAR denture base material. Methods: This study was a laboratory experiment conducted with samples measuring 60 mm x 6 mm x 4 mm, following ISO 20795-1 standards. A total of 30 samples were divided into three groups: a control group, 1% chitosan nano gel group, and a 1.25% chitosan nano gel group. The sample size was determined using the Federer formula. The impact strength of the samples was tested using a Charpy tester, and the data were analyzed by one-way ANOVA test. Results:  The impact strength of HPAR in the control group and the two treatment groups (1% and 1.25% chitosan nano gel) were 7.25 x 10-3 J/mm2, 10.17 x 10-3 J/mm2, and 9.07 x 10-3 J/mm2, respectively. The addition of chitosan nano gel to the HPAR denture base material significantly increase the impact strength (p = 0.001; p < 0.05). Conclusion: The incorporation of chitosan nano gel into the HPAR denture base material enhances impact strength, with the highest impact strength observed at a concentration of 1% chitosan nano gel.KEY WORDS: Chitosan nano gel, heat-polymerized acrylic resin, impact strengthEfek penambahan kitosan nano gel pada bahan basis gigi tiruan resin akrilik polimerisasi panas terhadap kekuatan impak: Studi eksperimentalABSTRAKPendahuluan: Resin Akrilik Polimerisasi Panas (RAPP) merupakan bahan basis gigi tiruan yang paling banyak digunakan pada pembuatan basis gigi tiruan karena beberapa keunggulan yaitu tidak bersifat toksik, biokompatibel, mudah didapat, dan estetik yang baik. Meskipun demikian, RAPP juga memiliki kelemahan yaitu kekuatan impak yang rendah akibat pemakaian gigi tiruan jangka panjang, sehingga diperlukan bahan penguat berupa kitosan nano gel. Tujuan penelitian ini untuk menganalisis efek penambahan kitosan nano gel pada bahan basis gigi tiruan RAPP terhadap kekuatan impak. Metode: Jenis penelitian ini adalah eksperimental laboratoris dengan sampel ukuran 60mm x 6mm x 4mm berdasarkan ISO 20795-1. Total 30 sampel dengan konsentrasi kontrol, kitosan nano gel 1%, dan 1,25%. Rumus besar sampel menggunakan rumus Federer, kemudian uji kekuatan impak sampel diuji dengan alat Charpy tester. Data dianalisis dengan uji ANOVA satu arah. Hasil: Nilai kekuatan impak RAPP kelompok kontrol dan kedua kelompok perlakuan penambahan kitosan nano gel 1% dan 1,25% adalah 7,25 x 10-3 J/mm2, 10,17 x 10-3 J/mm2, dan 9,07 x 10-3 J/mm2. Penambahan kitosan nano gel pada bahan basis gigi tiruan RAPP dapat meningkatkan kekuatan impak secara signifikan (p=0,001 (p<0,05)). Simpulan:  Penambahan kitosan nano gel pada bahan basis gigi tiruan RAPP berpengaruh dalam meningkatkan kekuatan impak dengan nilai kekuatan impak tertinggi pada konsentrasi 1%KATA KUNCI: Kitosan nano gel, kekuatan impak, resin akrilik polimerisasi panas.